Longitudinal changes of cognitive deficits and treatment outcome of cognitive behavioral therapy for major depression - Bernhardt, Maren; Schwert, Christine; Aschenbrenner, Steffen; Weisbrod, Matthias; Schröder, Annette (The journal of nervous and mental disease, 2021)
The current study examined neuropsychological changes over the course of cognitive behavioral therapy (CBT) in outpatients with major depressive disorder and the influence of cognitive deficits as predictors of clinical outcome in depression. A neuropsychological test battery was carried out on depressed outpatients (N = 54) at the beginning and at the end of CBT. Small improvements were found in divided attention, figural memory, and processing speed from pre- to posttreatment. Cognitive deficits in executive functions before treatment predicted the clinical outcome at the end of CBT. The present study reveals that attention and memory deficits are most likely to improve over the course of treatment, whereas executive functions remain stable in the long term. Depressed patients with worse executive functions at the beginning of treatment seem to benefit more from long-term CBT therapy.
Gesehen am 25.06.2021